Nok Kacung: Tourism Promotion Strategy Through Instagram Social Media - Crusitha Ken Ayu Putri Gunawan; Dedet Erawati (CV. Media Digital Publikasi Indonesia, 2026)
Social media has become one of the most prominent tourism marketing channels, including Instagram whose main medium is photo sharing. This study aims to describe the strategies used by the Nok Kacung community in Cirebon regency to develop cultural-based tourism through their Instagram account @nokkacungcirebon, as well as the role of this community. Qualitative approaches were used in this research, including non-participant observation of Nok Kacung instagram (ig) account as well as intensive interviews throughout the collection data process about content release and management done by 2022-2024. The effectiveness of th eInstagram account will be analysed through an interactive model suggested by Mile and Huberman, so called social technology introduced in a paper written by Richard Blundel whose marketing strategies on the new media are regularly shared by Kotler and Keller; being ideas of community-based tourism demystified. The findings from the use of promotional strategy by Nok Kacung are in five significant purposes on social media marketing: function of content creator, audience engagement, group building, reinforcing brand awareness, and transforming.